Understanding the use of mobile wireless technology in higher education: a case study of public university student in Malaysia - Mohammed Rawash, Fouad Mahmoud; Syed Hassan, Sharifah Sariah; Hashim, Che Noraini; Abdullah, Norillah (SCIENCEDOMAIN international, 2015)
This study investigated the use of Mobile and Wireless Technology (MWT) in higher education using the selected public university students in Malaysia. A random sampling has been selected among 490 students from three Public Universities and one Polytechnic. The study has been addressed to focus on the applications of MWT in learning and to identify the significant differences between gender and level of studies when using the learning applications via MWT. Using descriptive statistics, Independent t test, Analysis of Variance (ANOVA) and Post Hoc mean comparison test, this study highlighted the low level of MWT usage among students. Among other findings are the differences between gender and level of studies only related to specific learning activities. Implications of the study were discussed.